(untitled) (Bangladesh Journal of Animal Science, 2023)
The survey was conducted to represent the livestock production scenario and to know the performances of cattle and goats in few selected rural areas of Gaibandha district. The data on productive and reproductive performances of cattle and goats were collected from 102 household within four selected village under Gobindaganj Upazila of Gaibandha district with a pretested survey questionnaire. The collected data were compiled, tabulated and analyzed by student t test. In the study area, about 59% were indigenous cattle and 41% were crossbred cattle. A total of 113 goats were found in the study area of which 82% belongs to Black Bengal goat and the remaining 18% belongs Jamunapari goat. All the livestock (100%) were managed intensively during the spring and rainy seasons. Similarly, almost all livestock (100%) are confined in shed at night, and 45.9% and 54.09% of the livestock population are confined in shed and paddock at day time, respectively. Artificial insemination (AI) is the preferred breeding method for cattle, whereas goats primarily rely on natural mating. Milk yield and lactation period of cow, and mature body weight of both male and female were significantly (P<0.05) higher in crossbred than indigenous cattle. Similarly, age at first kidding, lactation period and kidding interval of does, and mature body weight of buck and does were significantly higher in Jamunapari goats than Black Bengal goats. However, the conception rate and number of kids per kidding were higher in Black Bengal goats than Jamunapari goats. In conclusion, from our results, crossbred cattle and Jamunapari goats are performing better in rural conditions, whereas Black Bengal goats are efficient in producing more offspring at a given time. Bangladesh Journal of Animal Science 52 (3): 78-84.